REDESAIN WORKSTATION COPY CENTER PERPUSTAKAAN UNIVERSITAS SURABAYA - Belinda Angela; Elieser Tarigan; Wyna Herdiana (CALYPTRA, 2018)
Library facilities that can support the activities of the visitors is Copy Center. The current Copy Center is not yet fully utilized by readers. Not all visitors who come to know the existence of the Copy Center service. Currently, the existing Copy Center is not able to organize all the copying support equipment, it causes the space in the Copy Center to look untidy and messy because of the many equipment and personal items of employees who are scattered. Unwittingly, the display of Copy Center can affect and reduce the beauty and comfort of the library space so the need to be redesigned on existing products. The purpose of this research is to design redesign of workstation copy center of University of Surabaya Library that can organize all photocopy support equipment to improve work efficiency without neglecting aesthetic element in product. Research methods used in data search are interviews, research library, and observation of existing products. The results of research conducted in the form of workstations designed in accordance with the workflow, using a design concept that combines futuristic and modern style. There is storage for storing stationery and photocopying equipment so that it can organize all the equipment to look neat. With this workstation, can improve the efficiency of employees working Copy Center.